Efetividades e entraves do programa Bolsa Família no município de Matão/SP: um olhar sobre a segurança alimentar dos beneficiários - Aquino, Lígia Maria de (Universidade Federal de São Carlos, 2024)
This study aims to discuss the main effectivenesses and institutional and organizational barriers of the Bolsa Família Program in the municipality of Matão/SP, focusing on elements of food security treated comprehensively. For this purpose, interviews were conducted with 100 beneficiary families (holders) through the application of semi-structured forms, and information was collected from the manager responsible for the local program. The sample size was defined using the method of stratified proportional probability sampling to the number of families served by the Social Assistance Reference Centers (CRAS) in the municipality. For the development of the work, a combination of quantitative and qualitative analysis of data from field research was used. Quantitative techniques were based on validated methodologies, such as the Food Network of the State University of Campinas (UNICAMP), which includes the Brazilian Food Insecurity Scale (EBIA) method, using a form applied to beneficiary families of the program in a stage preceding the qualitative techniques. These were adopted through semi-structured interviews with the local manager of the municipality's program in Matão. Through the collection and analysis of data, both qualitative and quantitative results were obtained on the socioeconomic and sociodemographic profile of the beneficiaries, as well as their perceptions and the manager's perception regarding the program and the responsible entities, which provided some recommendations for these public policies. The results indicate that, although the majority of family resources are allocated to food, food insecurity prevails in 96% of families. This highlights the importance of the program in immediately improving the adverse living conditions of families, however, by itself, it does not guarantee their food security. Therefore, it is crucial to integrate the program with other public policies related to education, health, food security, training, job creation, and income generation. Additionally, the establishment of a department or sector responsible for food security in the municipality is essential.
Effectiveness and obstacles of the Bolsa Familia program in the municipality of Matão/SP: a look at the food security of beneficiaries
Keywords: Avaliação de políticas públicas; Programa Bolsa Família; Efetividades; Entraves; Segurança alimentar e nutricional; Evaluation of public policies; Bolsa Familia Program; Effectiveness; Obstacles; Food and Nutrition Security; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::ORGANIZACOES PUBLICAS; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::POLITICA E PLANEJAMENTO GOVERNAMENTAIS